Design of AGV systems in working environments shared with humans: a multi case study. Issue 2 (2020) - Zuin, S.; Hanson, R.; Battini, D.; Persona, A.
Abstract: To meet the challenges and needs of an ever-changing market and as part of the fourth industrial revolution, factories are transforming into increasingly automated environments. A widely used and well-established solution today is Automated Guided Vehicles (AGVs), which often work closely with humans in crowded environments. Thus, in addition to flexibility, another important criterion associated with automatic handling systems is safety. The purpose of this work is to show how the involvement of three different but equally important roles in the design of an AGV system can benefit the whole project. The advantage of considering three different perspectives is the possibility of obtaining a more complete vision from the earliest stages of implementation, avoiding, as far as possible, the need to make changes in the next stages, which would generate higher costs than necessary. The article is based on two case studies, each one set in a major European manufacturing company: the first one is an Italian automotive manufacturer and the second one is a Swedish manufacturer of mechanical components. Both case companies apply AGVs in their material handling processes and, accordingly, have experience of both implementing and operating AGV systems. The article applies semi-structured interviews to study the three key roles, highlighting the key points for each role and showing the common issues that emerged from the interviews.